Practical reduction of manganese oxide - Sesen, Fikri Erdem (Allied Academies, 2017)
Manganese is an important metal used in steel industry. It is abundant in steel as an alloying element. Additionally, it is used as a deoxidiser in steel production. In steel industry, manganese metal is used as an intermediate product of ferromanganese. Ferromanganese is generally produced by reduction of oxidised manganese. Reduction is in the form of either metalothermic reduction or carbothermic reduction. Practically, metallographic reduction is performed with silicon or aluminium which form more stable oxides than magnesium. Carbothermic reduction means reduction with carbon. All of the reduction reactions are highly endothermic and a high amount of thermal energy is required for the accomplishment of these reactions [1, 2]. The most abundant forms of the manganese oxides are MnO2, Mn2O3, Mn3O4 and MnO. These compounds dissociate during heating.